CREATIVE CENTER DESIGN IN GEDEBAGE DISTRICT, BANDUNG CITY WITH CONTEMPORARY ARCHITECTURE - Ahmad Faqih Khatami; Harfa Iskandaria; Tri Endangsih (MAESTRO, 2023)
Bandung city is one of the creative cities in Indonesia. The creative industry is the main pillar in developing the creative economy sector which has a positive impact on life. The Indonesian government realizes that the creative economy focuses on the creation of goods and services by relying on creativity, talent and expertise as intellectual property. The amount of creativity in the city of Bandung has made the city of Bandung selected as a pilot project for creative cities throughout Asia Pacific. One way for the city of Bandung to achieve success in developing the image of the city of Bandung as a creative city is highly dependent on existing human resources, namely the creative community. The creativity of the people of the city of Bandung supports the development of the creative economy as a local sector that has wide potential. The construction of the Creative Center in the city of Bandung is not only used as a forum, but can be used as a training facility. Apart from that, it can accommodate creative economic activities which can be a place for craft synergy and collaboration and is supported by infrastructure that can make users of this building feel comfortable.